Evolving Role of Exercise Testing in Contemporary Cardiac Rehabilitation. Issue 5 (September 2016) - Reeves, Gordon R.; Gupta, Shuchita; Forman, Daniel E.
Abstract : Symptom-limited (maximal) exercise testing before cardiac rehabilitation (CR) was once an unambiguous standard of care. In particular, it served as an important screen for residual ischemia and instability before initiating a progressive exercise training regimen. However, improved revascularization and therapy for coronary heart disease has led many clinicians to downplay this application of exercise testing, especially because such testing is also a potential encumbrance to CR enrollment (delaying ease and efficiency of enrollment after procedures and hospitalizations) and patient burden (eg, added costs, logistic hassle, and anxiety). Nonetheless, exercise testing has enduring value for CR, especially because it reveals dynamic physiological responses as well as ischemia, arrhythmias, and symptoms pertinent to exercise prescription and training and to overall stability and prognosis. Moreover, as indications for CR have expanded, the value of exercise testing and functional assessment is more relevant than ever in the growing population of eligible patients, including those with heart failure, valvular heart disease, and posttransplantation, especially as current patients also tend to be more clinically complex, with advanced ages, multimorbidity, frailty, and obesity. This review focuses on the appropriate use of exercise testing in the CR setting. Graded exercise tests, cardiopulmonary exercise tests, submaximal walking tests, and other functional assessments (strength, frailty) for CR are discussed. Abstract : This review discusses the use of various types of exercise testing and other functional performance assessments in the context of cardiac rehabilitation programs. Tests discussed include the graded exercise test, cardiopulmonary exercise test, 6-minute walk test, and assessments of frailty and functional performance. Advantages and disadvantages of these tests are presented.